(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Depression is a prevalent disorder of mental health with a highly multifaceted pathogenesis thus finding an effective therapy for it remains a challenge. Depression is associated with downregulation of AMPK signaling pathways and lowers AMP/ATP and ADP/ATP ratios. Brain AMPK pathway malfunction and metabolic imbalances induce depression. The Unpredictable Chronic Mild Stress (UCMS) model was created centered on the predisposition of the stress-associated assumption of depression. SGLT2 inhibitor drugs canagliflozin and remogliflozin enhance brain AMPK signaling, reduce oxidative stress, increase neurotransmitters, and improve metabolism. SGLT2 inhibitor drugs have promising anti-depressant effects. Thus, in this investigation, we examined Sodium-glucose co-transporter-2 inhibitors to ameliorate depression symptoms in mice induced by unpredictable chronic mild stress by improving AMPK signaling. Seven groups of male mice (Swiss albino) were divided into (n=6). The disease groups received different stressors (unpredictable chronic mild stress model) for one week to produce depression, while normal control groups got 0.5% w/v Saline (orally). The standard group received Fluoxetine (10 mg/kg, orally), while the treatment groups were given canagliflozin (15 and 30 mg/kg, orally) and remogliflozin (10 and 30 mg/kg, orally). Behavioral parameters were assessed for induction of depression. Treatment with SGLT2 inhibitors showed significant (p < 0.05) antidepressant effects on behavioral, oxidative stress, neurotransmitter, brain histopathology, and gene expression evaluation of AMPK, mTOR, BNDF, and TNF-α levels. The current study found that SGLT2 inhibitor drugs have the potential to improve the AMPK signaling pathway and alleviate depression.